Microcystic adnexal carcinoma with mandibular bone marrow involvement - a case report with immunohistochemistry - Nagatsuka, H.; Rivera, R.S.; Gunduz, M.; Siar, C.H.; Tamamura, R.; Mizukawa, N.; Asaumi, J.; Nagai, N. (2006)
Microcystic adnexal carcinoma is a rare, locally aggressive cutaneous neoplasm with a high probability of persistence locally but a low probability of metastasis. We report a case of a 69-year-old female patient with an indurated plaque at the mental region. Histologically, the tumor cells invaded the subcutaneous tissue and mandibular bone. The tumor consisted mainly of squamous and basaloid epithelial nests and cords embedded in a desmoplastic stroma. A few keratin-filled microcysts and ductal structures were also observed. Perineural encroachment was also noted but there was no mitosis, cytologic features of malignancy, or metastasis. The epithelial nests were positive to various cytokeratins except for CK20 and the lumina of the ductal structures were positive to carcinoembryonic antigen. Our results indicate that microcystic adnexal carcinoma consists of tumor cells capable of both follicular and eccrine differentiation. It is locally aggressive, extends far beyond its clinical presentation and may involve the bone. It may persist and remain asymptomatic for so many years without metastasis. A lifetime postsurgery monitoring is mandatory to ensure early and proper management.